2020
DOI: 10.1177/1455072520947249
|View full text |Cite
|
Sign up to set email alerts
|

Levels of mental distress over 18 years after entering treatment for substance use disorders: A longitudinal cohort study

Abstract: Aims: The aims were to investigate whether baseline characteristics and problematic substance use were related to change in mental distress over time in patients with substance use disorders during an 18-year period. Method: This was a prospective, longitudinal study of patients followed for 18 years after entering specialised treatment for substance use disorders. A sample of 291 patients was recruited in 1997 and 1998. Mental distress was measured using the Hopkins Symptom Checklist 25 at baseline, and at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…In line with prior research including SUD inpatient treatment samples [12,13,17] patients with COD had indications of persistently poorer psychological functioning in terms of higher levels of mental distress, as compared to patients without COD. This finding underscores the need for SUD treatment providers to attend to mental health problems among patients with COD, and also alludes to the importance of available and accessible community mental health services upon discharge from the inpatient stay.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In line with prior research including SUD inpatient treatment samples [12,13,17] patients with COD had indications of persistently poorer psychological functioning in terms of higher levels of mental distress, as compared to patients without COD. This finding underscores the need for SUD treatment providers to attend to mental health problems among patients with COD, and also alludes to the importance of available and accessible community mental health services upon discharge from the inpatient stay.…”
Section: Discussionsupporting
confidence: 75%
“…Studies investigating psychological characteristics among patients with and without COD consistently showed that those with COD reported higher levels of general mental distress, [12][13][14]17]. Anxiety and depression are the two most frequently co-occurring psychiatric disorders among SUD patients [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study’s results align with prior clinical and population-based research on the prevalence and developmental trajectories of mental illness, affirming that mental health problems among patients with SUD are substantial and that mental health problems act as a risk factor for later life mental health problems [ 15 , 17 , 123 125 ]. It is also noted that in accordance with the recommended cut-off scores from SCL-90-R [ 76 ], a substantial proportion (76%) of the participants reported a level of psychological distress at treatment initiation that warrants further assessment.…”
Section: Discussionsupporting
confidence: 77%
“…This suggest that a two-step screening-diagnostic assessment procedure may be redundant for patients with pSUD and that a comprehensive diagnostic assessment of mental illness could represent a more cost-efficient approach in treatment planning for all patients with pSUD. Unsurprisingly, the study reinforces the well-documented association between substance intake and greater levels of psychological distress [ 15 , 17 , 130 ].…”
Section: Discussionsupporting
confidence: 76%